The effects of a standardized health education on the level of competency and perception of self-confidence in performing breast self-examination among adolescents, young adults, middle-age and elderly women of phase V, Sitio Lukban, Bagong Nayon, Antipolo Rizal - Reyes, Marina Lourdes M. (1992)
Education is a vital process in human growth and development. Progress and survival in a highly competitive world such ours require a more appropriate, relevant and realistic form of education in delivering important information to the public.Patient teaching is an integral part of patient care. The use of a standardized health education in patient teaching is the key to the success of innovative and preventive interventions such as breast self-examination (BSE).This study aimed to decrease cancer risk by early detection through the use of a standardized health education that will improve the accuracy in BSE practice. It emphasizes the nurse's role in assisting women with a very high risk of developing breast cancer. It recognizes perception of self-confidence as a critical factor in BSE performance.They study was community based. Cases were taken from a sub-urban community Phase V Sitio Lukban, Antipolo, Rizal. The sample consisted of 50 women. Data collection lasted from September to November 1991.The conceptual framework was based on the assumption that accuracy in BSE is dependent on the women's level of competency and perception of self-confidence in performing BSE as influenced by a standardized health education. Hypotheses used were organized according to the objectives and framework of the study. The variables studied included standardized health education, level of competency and perception of self-confidence, accuracy in BSE and demographic characteristics like age, marital status, education, and socio-economic status based on the monthly gross income of the head of the household. Instruments used in the study consisted of the observational checklists, forced-choice items questionnaires validated by on the spot home visits to the selected households of the respondents only one respondent was taken in each household.Statistical tests used to determine relationships and significant difference between or among the variables were percentage-ratio, paired t-tests, Pearson product moment correlation and analysis of variance (ANOVA).
The p<.05 level of significance was specified for all statistical tests. The results of the study are the following: 1. It is a significant relationship between a standardized health education and level of competence in BSE performance. The post-text scores in the following areas were higher than the pre-test scores: KNOWLEDGE: a. Prognosis of cancerb. Cancer causationc. Age, family history of cystic disease, obesity, parity & pregnancy & menopause as risk factors.d. Location of lumpe. Prognosis if with a lumpf. Bump or blow on the breastg. Use of tight fitting braSKILLS:a. Timingb. Preparation to BSEc. Use of towel / small pillowd. Movement of hand during palpatione. Dividing breasts into quadrantsf. Hand to be used in palpationg. Techniques of BSEATTITUDES:a. Willingness to be helped by a health workerb. Effect of mediac. Performing BSE aloned. Shares information with otherse. Consults with a specialistAll the other items did not show significant relationships. 2. There is a significant relationship between a standardized health education and perception of self-confidence in performing breast self-examination. The scores were summated. The post-test scores were higher than the pre-test scores in most of the items.3. There is a significant difference in the level of competency and perception of self-confidence among women performing BSE. For the level of competency, the paired T-test revealed a T-value of 10.174 for knowledge, 6.64 for skills and 10.52 for attitudes as compared to the tabular value of 2.0 df = 49 at p < .05 level of significance. For the perception of self-confidence, the T-test revealed a t-value of 113.24.4. There is a significant relationship between the level of competency and perception of self-confidence in BSE. The r-value was 0.234. There was a positive correlation, however, it is low. This means that knowing BSE does not necessarily mean one is performing it or doing it with accuracy.5. There is no significant difference between / among the age groups, marital status, education, and socio-economic status of women performing BSE. The analysis of variance did not show any significant difference in the pre and post test scores considering demographic characteristics as variables.Implications of the study showed that the level of competency in performing BSE is significantly related to the variable of standardized health education.Thus, competencies needed in the promotion of innovative and preventive health behaviors such as BSE could be improved through the use of a standardized health education rendered by a nurse.Recommendations of the study were focused on the enhancement of quality nursing care through the improvement of women's level of competency and perception of self-confidence and preventive health behavior such as BSE by improving accuracy in the procedure.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Patient care; Breast -- Examination; Health education